The Verrucaria aethiobola group (lichenised Ascomycota, Verrucariaceae) in North-west Europe - Orange, Alan (Phytotaxa, 2020)
Material which has been ascribed to the freshwater species Verrucaria aethiobola or V. latebrosa is shown to comprise three cryptic species, based on ITS and mtSSU sequences. The names V. aethiobola and V. latebrosa are applied to two of these, and epitypes are selected to fix the application of the names. The third cryptic species is described as V. tephromela. In addition, V. anziana is confirmed as a separate species, of which most specimens can be identified by the thick thallus and poorly developed involucrellum. A related non-aquatic species found on calcareous stones is described as V. pallidomurina.